POLICY FOR DEVELOPMENT OF SHARIA BANKING OPERATING SYSTEM - Mustafa Mustafa (Sean Institute, 2022)
Banking and financial institutions are highly regulated industries, moreover Islamic banking is not only bound by positive legal signs, the operational system of Islamic banks is also closely tied to God's law, whose violation results in harm in the world and the hereafter. Because of the unique regulations that enclose all Islamic banking transactions, this study will try to discuss the implementation of contracts that can be carried out in Islamic banks. In order to avoid the payment and receipt of usury and/or interest, in carrying out funding and financing activities, sharia banking uses a profit sharing investment mechanism to fulfill capital needs (equity financing) and investment based on costs. (fee based investments) through a buying and selling mechanism (al bai') to fulfill financing needs (debt financing)